Hubungan antara coping strategy dengan parenting stress pada ibu yang memiliki anak autis - Febriana Trias Rahmawati (Cognicia, 2019)
Mothers who have autistic children are not easy to care for. Different treatments, special care for autistic children who have complex conditions different from normal children is what makes parents experience parental stress, especially mothers. One way to deal with maternal parenting stress is by using coping strategies. The purpose of this study was to determine the relationship between coping strategies and parenting stress on mothers with autistic children and to find out how strong the relationship of coping strategies is problem focused coping with emotion focused coping to the level of parenting stress in mothers with autistic children. This research is a quantitative correlational study using the subject of 60 mothers who have autistic children. The sampling technique used is sampling quota where the sampling technique is determined from a population that has certain characteristics to the desired number (quota). This research method uses 2 scales, namely Brief COPE and PSI-SF. While the data analysis used in this study isanalysis product moment using SPSS 25. The results obtained a significant value of 0.01 <0.05 and r value of 0.601 which means there is a positive relationship between coping strategies with parenting stress in mothers who have autistic children. The contribution of coping strategies to parenting stress is 36.1%.